EFFECT OF TREATMENTS FOR SOURSOAP SEED DORMANCY BREAKING AND EMERGENCY - Bagatim, Amanda Garcia [UNESP]; Nacata, Guilherme [UNESP]; De Andrade, Renata Aparecida [UNESP] (Interciencia, 2016)
This research aimed to test the effect of different treatments for dormancy breaking in soursop seeds and their effect on early germination, thus evaluating seedling emergence. The experiment was realized using seeds obtained from ripe fruits, washed in running water until completely clean and free of mucilage, and then dried in the shade. The seeds were subjected to four treatments: cutting of the distal region of the seeds, low temperature (-10 degrees C) for 24h, immersion in water for 24h, and scarification with sandpaper No 10, plus a control treatment. Each treatment consisted of 4 replicates, with 10 seeds in each one. The evaluation was performed weekly, counting the number of seed Zings emerged and determining the emergence percentage for every treatment. From the results it can be concluded that in order to obtain higher rates of emergency in soursop, prior treatment using seed scarification with sandpaper is recommended.